Kemampuan Berpikir Kritis Siswa Melalui Model Problem Based Learning Berbantuan Talking Stick - Sri Suryaningsih; Sri Ngabekti; Amin Yusuf (Universitas Negeri Makassar, 2021)
This study aims to analyze the use of Problem Based Learning (PBL) models assisted by Talking Sticks in improving students' critical thinking skills. The method in this study is a quantitative Quasi-Experimental Non-equivalent Pretest and Posttest Control-Group Design. The research sample was the fifth-grade students of SDN 2 Sape and SDN INPRES Sangia as the experimental class with a total of 54 students while the fifth-grade students of SDN 8 Sape with SDN INPRES Dea as the control class amounted to 37 students. Data collection is using a critical thinking ability test sheet. The data obtained were analyzed using N-gain with the achievement of students' critical thinking skills in the experimental class with an average increase of 0.40 in the medium category and the control class getting an average increase of 0.16 in the low category. Students must be trained by giving critical thinking questions and by learning while playing will involve students actively in solving various kinds of problems and involve students to learn directly with the real world. The benefits of research as a reference for learning models and the creation of fun science learning.